STRATEGI GURU DI MASA DAN PASCA PANDEMI PENGAJARAN MUSIK ANAK USIA DINI - Panjaitan, Sarah; Safrina, Rien; Budiawan, Hery (Program Studi Pendidikan Musik, 2024)
The purpose of this study is to find out the strategies applied by teachers in early childhood music learning during and after the pandemic. The research method used in this study is the Literature Review method with narrative analysis techniques systematic review. The data comes from the results of existing research and is obtained from google search engines, google scholar, semantic scholar, researchgate and sage journals and books on learning strategies. Place and Time the Research was held in South Jakarta, Jakarta from September 2022 to January 2023. Data Collection is carried out by taking 15 articles which are processed by simplifying, systematically modernizing data in order to answer problems in research, which is then analyzed by providing logical arguments. The Object of Research is the teacher's strategy. Data Analysis is carried out by making notes and giving color to each category and then summarizing, presenting, and drawing conclusions. The results of this study are the strategies used by teachers during the pandemic in teaching early childhood music, namely inquiry learning strategies, quantum learning strategies, and integrated art learning strategies through singing and moving activities or dancing to music and post-pandemic, namely expository learning strategies, cooperative learning strategies, integrated art learning strategies, and active learning strategies through singing and playing music activities.